WORD-TARGET AND PLEASURE READING: EXPLORING EXTERNAL MOTIVATION IN L2 READING - Lanoke Intan Paradita; Nurul Hunafa; Dita Surwanti; Mariska Intan Sari; Puthut Ardianto (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2023)
ABSTRACTThis preliminary study explores external motivation in L2 extensive reading regarding word-target and pleasure reading. In contrast to the extensive reading principle which discourages the use of assessment to promote pleasure in reading, this study aims to explore how reading targets as one form of assessment is potential to maintain pleasure in reading. This qualitative study was conducted in the Department of Arabic Education at an Islamic private university in Yogyakarta, Indonesia. Two reading classes for first-year students were observed. The data were collected from observation, interviews, and students’ reading profiles as recorded in XReading, a learning management system supporting students’ reading practice. The results show that the students use the reading target as an external drive to read and XReading allows students to choose the texts according to their preference and within their linguistic capacity, which instills pleasure in reading. The findings also suggest that a periodical goal and regular teacher monitoring will motivate students to sustain their reading progress. ABSTRAKStudi pendahuluan ini mengeksplorasi motivasi eksternal dalam membaca ekstensif dalam bahasa asing, terutama terkait dengan target kata dan kesenangan membaca. Berbeda dengan prinsip membaca ekstensif yang secara umum tidak menyarankan adanya asesmen untuk mendorong kesenangan membaca, penelitian ini bertujuan untuk mengeksplorasi bagaimana target membaca justru menjadi salah satu asesmen yang berpotensi untuk menjaga kesenangan membaca. Penelitian ini merupakan penelitian kualitatif yang dilaksanakan di Prodi Pendidikan Bahasa Arab di salah satu universitas swasta di Yogyakarta, Indonesia. Observasi dilakukan di dua kelas mahasiswa tahun pertama. Data yang dikumpulkan berupa data observasi, interview, profil membaca mahasiswa yang terekam dalam XReading, sebuah learning management system yang digunakan mahasiswa untuk mendukung praktek membaca ekstensif mereka. Hasil dari penelitian menunjukkan bahwa mahasiswa menggunakan target membaca sebagai dorongan eksternal untuk membaca dan XReading memberikan ruang pada mahasiswa untuk memilih bacaan sesuai dengan pilihan dan kemampuan linguistik mereka, yang menguatkan kesenangan mereka dalam membaca. Temuan dalam penelitian ini juga menyarankan adanya gol bacaan dan monitoring dosen secara berkala untuk memotivasi mahasiswa dalam mempertahankan progres membacanya.How to Cite:  Paradita, L.I, Surwanti, D., Hunafa, N.. Sari, M.I., & Ardianto, P. (2023). Word-target and Pleasure Reading: Exploring External Motivation in L2 Reading. IJEE (Indonesian Journal of English Education), 10(2), 487-502. doi:10.15408/ijee.v10i2.35426.